Information Rate-Harvested Power Tradeoff in THz SWIPT Systems Employing Resonant Tunneling Diode-Based EH Circuits - Shanin, Nikita; Clochiatti, Simone; Mayer, Kenneth M.; Cottatellucci, Laura; Weimann, Nils G.; Schober, Robert (IEEE transactions on communications, 2025)
In this paper, we study terahertz (THz) simultaneous wireless information and power transfer (SWIPT) systems. Since coherent information detection is challenging at THz frequencies and Schottky diodes may not be efficient for THz energy harvesting (EH), we propose a novel THz SWIPT system design that employs unipolar amplitude shift keying (ASK) modulation at the transmitter (TX) and a resonant-tunnelling diode (RTD)-based EH circuit at the receiver (RX) to extract both information and power from the received signal. Furthermore, we propose a novel model for the dependence of the instantaneous output power of the RTD-based RX on the instantaneous received power, which is based on a non-linear and non-monotonic piecewise function, whose parameters are adjusted to fit circuit simulation results. To determine the information rate-harvested power tradeoff of the considered THz SWIPT system, we derive the distribution of the transmit signal that maximizes the mutual information between the transmit and received signals subject to constraints on the required average harvested power at the RX and the peak signal amplitude at the TX. Since the computational complexity needed for maximization of the mutual information may be infeasible for real-time THz SWIPT systems, we derive low-complexity suboptimal input signal distributions that maximize an achievable information rate numerically and in closed form for high and low required average harvested powers, respectively. Furthermore, based on the obtained results, we propose a suboptimal closed-form distribution of the transmit signal which can also guarantee a desired harvested power at the RX. Our simulation results show that while the proposed EH model can capture the non-monotonicity of RTD-based EH circuits in the THz band, baseline linear and non-linear EH models, developed for Schottky-diode-based EH circuits, cannot. Furthermore, we demonstrate that a lower reverse current flow and a higher breakdown voltage of the employed RTD are preferable when the input signal power at the RX is low and high, respectively. We also show that all proposed input distributions yield practically identical SWIPT system performance. Moreover, we reveal that the information rate-harvested power tradeoff of THz SWIPT systems is determined by the peak amplitude of the TX signal and the maximum instantaneous harvested power for low and high received signal powers, respectively. Finally, we compare the proposed THz SWIPT system with two baseline schemes and confirm that the RX circuit parameters, mathematical EH models, and optimal transmit signal distributions have to be carefully designed to achieve high performance in THz SWIPT systems.